2021
DOI: 10.1080/17512786.2021.1913626
|View full text |Cite
|
Sign up to set email alerts
|

Changing the Beat? Local Online Newsmaking in Finland, France, Germany, Portugal, and the U.K

Abstract: Local news organizations are adapting their newsroom routines to better respond to a digital readership. These models feature different levels of online integration, but all aim to restructure newsroom responsibilities to ensure editorial and economic sustainability. This study uses a cross-national approach to assess how roles and structures in local and regional newsrooms are changing in the digital environment. In-depth interviews with managers, editors, and journalists in five countries (Finland, France, G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Drawing on interviews with journalists, editors, and other media workers in three diverse regional communities, Carson et al (2016) found practitioners were adapting to the more straitened financial environment by working more closely with community sources. In other parts of the world, Jenkins and Jeronimo (2021) have found a similar ability to adapt to new digital practices as newsrooms embrace online publication. While there has been a shift towards centralising news, and syndication to reduce costs and remain viable (Franklin, 2006), emerging research points to smaller, independent family-owned local media businesses as a possible road to financial security (O’Hara, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Drawing on interviews with journalists, editors, and other media workers in three diverse regional communities, Carson et al (2016) found practitioners were adapting to the more straitened financial environment by working more closely with community sources. In other parts of the world, Jenkins and Jeronimo (2021) have found a similar ability to adapt to new digital practices as newsrooms embrace online publication. While there has been a shift towards centralising news, and syndication to reduce costs and remain viable (Franklin, 2006), emerging research points to smaller, independent family-owned local media businesses as a possible road to financial security (O’Hara, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…We cannot ignore the fact that the use of geolocation technology is growing-to access news at the local level and even in situations where the media websites do not have a responsive design [40]. Still, at the reception level, we note the fact that a recent study, carried out in several countries, identified, precisely in Portugal, that the use of mobile apps by local media emerged as a way of concentrating the community of readers in an environment controlled by the media itself, contrary to what happens for example with Facebook and other social media [8].…”
Section: Contingencies and Limitations Of The Local Press: The Portuguese Casementioning
confidence: 83%
“…This has led many local Portuguese press organizations to close their doors due to their inability to adapt to this new context and to understand the preferences of online users. However, while many local newspapers are facing difficulties, new and innovative forms of news content and information access started to gain prominence in some countries, including Portugal [8]. Even if only residual, the production of mobile news appears as a new experience carried out by local journalists [9].…”
Section: Introductionmentioning
confidence: 99%
“…At this moment, when we are trying to portray the reality of the local media in Portugal, it is also important to highlight that the local media has received increasing attention from the academy, having grown, in recent years, the number of investigations that seek to characterize professionals and their working conditions (Jerónimo et al 2022a;Morais et al 2020), but it is also important to study the challenges introduced by digital (Jerónimo et al 2022c;Jenkins and Jerónimo 2021;Carvalheiro et al 2021;Campos and Jerónimo 2019) and the sustainability of the local media business itself (Morais et al 2020;Jerónimo and Correia 2020;Ramos and Correia 2020;Quintanilha et al 2019;Cardoso et al 2017), without forgetting the studies and the analyses that focus on the growth of misinformation in these media (Jerónimo and Esparza 2022;Correia et al 2019). Even when we consider the studies that seek to analyze the state of journalism in a more general way, more and more emphasis has also been given to local media professionals and their problems in particular moments, such as the one that occurred during the pandemic (Newman et al 2022;Cardoso et al 2021;Camponez et al 2020).…”
Section: The Reality Of Local Media In Portugalmentioning
confidence: 99%